The drunken monkey : why we drink and abuse alcohol - Dudley, Robert, 1961- (University of California Press, 2014)
Alcoholism, as opposed to the safe consumption of alcohol, remains a major public health issue. In this accessible book, Robert Dudley presents an intriguing evolutionary interpretation to explain the persistence of alcohol-related problems. Providing a deep-time, interdisciplinary perspective on today's patterns of alcohol consumption and abuse, Dudley traces the link between the fruit-eating behavior of arboreal primates and the evolution of the sensory skills required to identify ripe and fermented fruits that contain sugar and low levels of alcohol. In addition to introducing this new theo.